Diffusion‐weighted chemical shift imaging of human brain metabolites at 7T. Issue 6 (1st July 2014) - Ercan, Ayse Ece; Techawiboonwong, Aranee; Versluis, Maarten J.; Webb, Andrew G.; Ronen, Itamar
<x xml:space="preserve">Abstract</x> Purpose Diffusion‐weighted chemical shift imaging (DW‐CSI) of brain metabolites poses significant challenges associated with the acquisition of spectroscopic data in the presence of strong diffusion weighting gradients. We present a reproducible DW‐CSI acquisition and processing scheme that addresses most of the potential sources of instability and provides reproducible and anatomically meaningful diffusion‐weighted and apparent diffusion coefficient (ADC) metabolite maps. Methods A real‐time navigator‐based acquisition scheme was used, allowing instantaneous reacquisition of corrupted k‐space data and postprocessing correction of gradient‐induced phase fluctuations. Eddy current correction based on residual water resonance was implemented and improved the quality of the data significantly. Results Highly reproducible diffusion‐weighted metabolite maps of three highest concentration brain metabolites are shown. The navigator‐based accept/reject strategy and the postacquisition corrections improved the stability of the DW‐CSI signal and the reproducibility of the resulting DW‐CSI maps significantly. The metabolite ADC values could be related to the underlying tissue cellular composition. Conclusion Robust investigation of DW‐CSI of brain metabolites is feasible and may provide information complementary to that obtained from more sensitive but less specific methods such as diffusion tensor imaging. Magn Reson Med 73:2053–2061, 2015. © 2014 Wiley Periodicals, Inc.